What predicts attitudes toward computer? - Tengku Ariffin, Tengku Faekah; Nordin, Hasniza; Abdul Karim, Abdul Malek (Malaysian Education Deans' Council, 2008)
The study was conducted to examine the status of computer use and attitudes among secondary school students.It also identifies the relationships among the variables and the predictors of computer attitudes.External variables (such as computer experience and frequency of use), perceived usefulness and confidence are included as potential antecedents of attitudes toward computer. Data was collected among 293 secondary school students in Kedah, Malaysia. It was found that there exist moderate to strong relationships between all the variables studied, with r-value ranging from .17 to .69. Regression analyses have identified confidence in using computers as the strongest predictors of computer attitudes, with R2 = .48. Other variables, computer experience, perceived usefulness and frequency of use also entered the equation, but turned out to be poor predictor of attitude toward computers.Discussion of findings and suggestions for future research are included in the text.